An approach for Assessing Harmonic Emission Level Based on Robust Partial Least Squares Regression - Xiang Li; Minyou Chen; Yongwei Zheng; Shan Cheng; Feng Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
An approach to evaluate harmonic contributions at the point of common coupling is presented in this paper. The proposed approach is based on robust partial least squares regression, which estimates system harmonic impedance by utilizing the signals of harmonic voltage and current measured synchronously at the point of common coupling. Consequently according to the IEC Technical Report 61000-3-6 the harmonic emission level of user is calculated. The presented method overcomes the disadvantage of variable dependence in establishing of the system model and reduces or removes the effect of outlying data points. The method is verified through a simulation study and with extensive field measurements.